Factors affecting Women towards purchase of Facial skin care Product of Patanjali (A case study of Lalitpur) (Voice of Teacher, 2021)
It was understood that Women and girls being more concerned towards their beauty also seems true in reference to this study. This study has been able to show the increased interest of young girls towards the use of herbal cosmetics Product of minimize the side effects and enhancing their beauty. Similarly increasing influence of Patanjali Product in Nepalese young girls' life also has been traced through this study as many respondents have shown their trust towards the brand of Patanjali. Young /teen aged girls of Lalitpur seem to be highly influenced by their family members when it comes to use of cosmetics. Patanjali has been able to create the customers on the market who trust their brand because of various competitive advantages it owns in relation to other leading competitors like its natural indigents', strong image, popular figure.